2014
DOI: 10.1002/pi.4830
|View full text |Cite
|
Sign up to set email alerts
|

Polycondensation of structurally divergent tetraamine monomers with dicarboxylic acids to synthesize polybenzimidazole copolymers for polymer electrolyte membranes

Abstract: Polybenzimidazole copolymers were synthesized by varying compositions of tetraamines monomers in polymerization feed with a single dicarboxylic acid instead of conventional method where two acids were used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 61 publications
0
8
0
Order By: Relevance
“…It is widely known that polybenzimidazole is a hygroscopic polymer and it has a high affinity to form stronger intermolecular interactions with water molecules, which severely influences the dimensional stability of the membrane. After immersing the membranes in distilled water for 3 days, we observed that the amount of water uptake (WU) of PyOPBI, Me-PyOPBI, Ph-PyOPBI, and Ph­(CF 3 )-PyOPBI membranes is 13.21, 17.01, 20.55, and 16.56 wt %, respectively (Figure S9). It is quite evident from the data that the introduction of pendant type side groups in PyOPBI backbone has increased the WU; however, Ph­(CF 3 )-PyOPBI displays the least WU among the pendant type polymers because of the hydrophobic nature owing to the presence of trifluoro functionality in the polymer backbone.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…It is widely known that polybenzimidazole is a hygroscopic polymer and it has a high affinity to form stronger intermolecular interactions with water molecules, which severely influences the dimensional stability of the membrane. After immersing the membranes in distilled water for 3 days, we observed that the amount of water uptake (WU) of PyOPBI, Me-PyOPBI, Ph-PyOPBI, and Ph­(CF 3 )-PyOPBI membranes is 13.21, 17.01, 20.55, and 16.56 wt %, respectively (Figure S9). It is quite evident from the data that the introduction of pendant type side groups in PyOPBI backbone has increased the WU; however, Ph­(CF 3 )-PyOPBI displays the least WU among the pendant type polymers because of the hydrophobic nature owing to the presence of trifluoro functionality in the polymer backbone.…”
Section: Resultsmentioning
confidence: 97%
“…To address this concern, we recently synthesized pyridine-bridged PBI (PyPBI), which was obtained by poly condensing 2,6-bis (3′,4′-diaminophenyl)-4-phenylpyridine (PyTAB), a tetraamine monomer which was made readily, with varieties of dicarboxylic acids. Several PyPBIs synthesized so far showed good solubility and processability along with very good thermal, mechanical and chemical stabilities. However, it was observed that the membranes of PyPBI get dissolved in concentrated (85%) PA and therefore needs attention. Recently, we addressed this problem by cross-linking the PyPBI chains using BrPPO, but this approach hinders the solubility .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This can be accomplished by using different aromatic/aliphatic dialdehyde and tetraamine precursors (monomers) prior to the condensation polymerization. [27][28][29][30][31][32] Another synthetic method is N-substitution of PBI, which others have attempted with varying success. [33][34][35][36] Other PBI materials have been derived from synthetic techniques by crosslinking with other functionalized compounds, such as halogenated alkyl/phenyl compounds, aldehydes and alcohols.…”
Section: Introductionmentioning
confidence: 99%
“…Several modified PBI based membranes are reported in the literature. Pyridine based PBI membranes with improved proton conductivity and oxidative stability; membranes of PBI segmented block copolymers and random block copolymers of PBI by using tetra-amine and dicarboxylic acid combinations have also been synthesized and examined as their applicability in PEMFCs [20][21][22]. However, among the promising candidates, sulfonated poly (arylene ether sulfone)s (SPAES)s are well-known engineering thermoplastics and these are reasonably good choice for high temperature operating PEMFCs.…”
Section: Introductionmentioning
confidence: 99%